Pemilihan Sikat Gigi yang Sesuai dengan Usia Anak - Arianne Dwimega (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
ABSTRACTImportance of maintaining good oral hygiene is one of the basic underlying need to achieve oral health. The purpose of brushing teeth is to clean a child's teeth and mouth to prevent oral disease such as cavities. Highest prevention of cavities occurs when children regularly brush their teeth with the help and supervision of parents. To do so, parents especially mothers require sufficient information to guide their children to maintain their oral hygiene properly. One of which, is about choosing a toothbrush that is appropriate with the age of child. Toothbrush consists of 3 main parts namely the head, handle and bristles. These three components must be considered in choosing a toothbrush that is appropriate for a child. We also need to pay attention to size that is appropriate for the child. Various variables affect selection of a toothbrush. Dentists should assess individual needs of each patient before making recommendations to parents, especially mothers in choosing a toothbrush for their child.